2023
DOI: 10.1021/acs.est.2c07643
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nucleation of Supersaturated Water Vapor onto Sub-10 nm Nanoplastic Particles

Abstract: Nanoplastic pollution by atmospheric transport processes is a recently discovered environmental problem on a global scale that is attributed to the dispersion of aerosolized nanoplastics. However, knowledge about the basic physicochemical properties of aerosol nanoplastic particles is scarce. Here, we present experiments on the heterogeneous nucleation of supersaturated water vapor onto sub-10 nm polyethylene terephthalate (PET) seeds. We determined onset saturation ratios for the activation of PET seeds in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Micro- and nanoplastic particles have been reported to generate from incineration with the Raman spectroscopy method, agreeing with our ambient observation. Previous studies also have shown that nanoplastic particles comprised of both PS and polyethylene terephthalate (PET) can be generated at temperatures as low as 200 °C through homogeneous nucleation when the plastic is melted and cooled. , A waste incinerator can often be heated to 650 to 1100 °C, higher than the melting and vapor recondensation onset temperature of 200 °C from which nanoplastics can be generated. In addition, potential incomplete combustion in the incineration of waste further facilitates the generation of byproducts including nanoplastic particles. It is worth noting that the PS NPP concentration decreased significantly between 10 pm to 2 am from March 22–23, suggesting that the PS NPP enhancement intervals before and after this period were not due to the change of the boundary layer height but likely due to external sources of PS NPPs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro- and nanoplastic particles have been reported to generate from incineration with the Raman spectroscopy method, agreeing with our ambient observation. Previous studies also have shown that nanoplastic particles comprised of both PS and polyethylene terephthalate (PET) can be generated at temperatures as low as 200 °C through homogeneous nucleation when the plastic is melted and cooled. , A waste incinerator can often be heated to 650 to 1100 °C, higher than the melting and vapor recondensation onset temperature of 200 °C from which nanoplastics can be generated. In addition, potential incomplete combustion in the incineration of waste further facilitates the generation of byproducts including nanoplastic particles. It is worth noting that the PS NPP concentration decreased significantly between 10 pm to 2 am from March 22–23, suggesting that the PS NPP enhancement intervals before and after this period were not due to the change of the boundary layer height but likely due to external sources of PS NPPs.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies also have shown that nanoplastic particles comprised of both PS and polyethylene terephthalate (PET) can be generated at temperatures as low as 200 °C through homogeneous nucleation when the plastic is melted and cooled. 90 , 91 A waste incinerator can often be heated to 650 to 1100 °C, higher than the melting and vapor recondensation onset temperature of 200 °C from which nanoplastics can be generated. In addition, potential incomplete combustion in the incineration of waste further facilitates the generation of byproducts including nanoplastic particles.…”
Section: Resultsmentioning
confidence: 99%
“…25,26 Nevertheless, humans are exposed to airborne MPs and can therefore inhale them, posing potential health risks. [27][28][29] Even less is known about the possible implications of these particles on the microphysics of clouds as well as on precipitation and climate related processes, 30 e.g., nanoplastics can potentially act as cloud condensation nuclei 31 or nucleate ice heterogeneously. 32,33 The detection of atmospheric MPs is oen associated with labor-intensive and time-consuming procedures.…”
Section: Introductionmentioning
confidence: 99%
“…Even less is known about the possible implications of these particles on the microphysics of clouds as well as on precipitation and climate related processes, 30 e.g. , nanoplastics can potentially act as cloud condensation nuclei 31 or nucleate ice heterogeneously. 32,33…”
Section: Introductionmentioning
confidence: 99%
“…During the crystal growth process, heterogeneous nucleation or homogeneous nucleation is crucial . In heterogeneous nucleation, the formation of crystals does not begin with free molecules in the solution but rather with heterogeneous nuclei . In homogeneous nucleation, crystal formation originates from free ions, atoms, or molecules in the solution, and these molecules aggregate to form small nuclei …”
Section: Introductionmentioning
confidence: 99%